Correction: A heterometallic (Fe6Na8) cage-like silsesquioxane: synthesis, structure, spin glass behavior and high catalytic activity. Issue 57 (31st May 2016) - Bilyachenko, Alexey N.; Levitsky, Mikhail M.; Yalymov, Alexey I.; Korlyukov, Alexander A.; Vologzhanina, Anna V.; Kozlov, Yuriy N.; Shul'pina, Lidia S.; Nesterov, Dmytro S.; Pombeiro, Armando J. L.; Lamaty, Frédéric; Bantreil, Xavier; Fetre, Amandine; et al.
Abstract : Correction for 'A heterometallic (Fe6 Na8 ) cage-like silsesquioxane: synthesis, structure, spin glass behavior and high catalytic activity' by Alexey N. Bilyachenko et al., RSC Adv., 2016, 6, 48165–48180.